Scientific progress in small ruminants in the first decade of 21st century - Resende, Kleber Tomas de [UNESP]; Molina de Almeida Teixeira, Izabelle Auxiliadora [UNESP]; Biagioli, Bruno [UNESP]; Lima, Lisiane Dorneles de [UNESP]; Neto, Oscar Boaventura [UNESP]; Pereira Junior, Joao de Deus [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2010)
Worldwide interest in small ruminants has increased in recent years in both, the productive and scientific aspects. In Brazil, the same trend has been observed, however, among all small ruminants, goats and sheep can be highlighted. Thus, this review aimed to discuss scientific progress in goat and sheep in the last decade. Data were collected in different databases, such as Institute for Scientific Information (ISI), Scientific Electronic Library Online - SciELO, Coordenacao de Aperfeicoamento de Pessoal de Nivel Superior - CAPES, Instituto Brasileiro de Geografia e Estatistica - IBGE and Food and Agriculture Organization of the United Nations - FAO. In the last decade, goat and sheep have received particular attention from researchers, which can be proved by the number of publications involving these species, which increased 41% worldwide, and nationwide increase was even more expressive, 219%. Methodological aspects applied in researches have also improved, emphasizing multidisciplinary approach. Much of the scientific progress was due to increasing financial support through thematic calls demanded by society and by the productive chain of meat and milk. In these calls is noticeable the concern with product quality, competitiveness and sustainability.
Keywords: development; goat; scientific production; sheep